A 19F nuclear magnetic resonance study of uptake and metabolism of 5-fluorocytosine in susceptible and resistant strains of Candida albicans. - Di Vito, M (1986)
The metabolism of the antifungal drug 5-fluorocytosine (5-FC) was studied in intact viable cells of Candida albicans by 19F nuclear magnetic resonance (NMR). The uptake of the drug and its conversion to the deaminated product 5-fluorouracil (5-FU) were easily observed by NMR analysis of both the cells and the supernatants of the incubation mixture. In the 5-FC-resistant mutant D14 of C. albicans, which lacked cytosine deaminase activity, the resonance peak of 5-FU was not observed. In intact cells of all 5-FC-susceptible strains the metabolism of 5-FU progressed to the formation of other fluorinated derivatives which were visualized as a single, broad resonance band at a lower field with respect to 5-FC and 5-FU. This band was resolved into three distinct peaks in the acid extract of treated cells, one of these peaks being attributable to 5-fluoro-dUMP (5-FdUMP). In strain 72R of C. albicans, which is 5-FC resistant because of a low level of UMP-pyrophosphorylase activity, the broad, low-field resonance band was detected later and with much less intensity than in the 5-FC-sensitive strains. This suggests that, besides 5-FdUMP, this band is also contributed to by 5-FUMP and possibly other phosphorylated derivatives. 19F NMR analysis also revealed that a significant amount of 5-FU is secreted into the external medium, the rate of secretion being higher in 5-FC-resistant strain 72R than in 5-FC-sensitive strain 72S. Although not all resonances were definitely identified, this study shows that 19F NMR spectroscopy may be an important tool for noninvasive analysis of the metabolism of fluorinated drugs in yeasts.